The flexible routing with flex for the fast delivery - Park, TaeJoon; Chung, Yerim (韓國컴퓨터情報學會論文誌, 2021)
In this paper, we propose "flexible routing with flex" to provide fast delivery by using the flexible routing for the delivery vehicle and crowd-shipper named flex. To this end, we have introduced an algorithm that can build the delivery plan for delivery vehicles and flexes. The introduced algorithm uses the 2-opt algorithm to construct routes with low complexity and acceptable quality, and the revised saving algorithm to assign customer orders to the flex. The algorithm allows the vehicle and the flex to function complement each other without separating the delivery vehicle from the flex. The experiments consider the 3 different instances named Random, Mixed, Cluster, and show that "the flexible routing with flex" has a better result than "vehicle only". The sensitivity analysis of the flex cost and time penalty shows "the flexible routing with flex" can provide better service not only to the customers who are serviced by flex but also to the customers who are serviced by the delivery vehicle. 본 논문의 목적은 빠른 배송을 위한 배송 차량의 유연 회차와 크라우드쉬핑(Crowd Shipping) 배달원인 플렉스를 활용한 "유연 회차와 플렉스" 방식을 제안하고, 풀이 알고리즘을 제안하는 것이다. 알고리즘은 선행 연구에서 성능이 검증된 2-opt를 사용하여 차량 경로를 계산하고, 절약 휴리스틱(Saving heuristic)을 변형한 방식으로 플렉스에 할당할 고객을 계산한다. 알고리즘은 차량과 플렉스를 분리하는 것이 아니라, 상호 보완적으로 운용될 수 있게 한다. 이를 위해 차량 정보가 플렉스 할당 과정에 고려되도록 하였다. 본 연구의 실험은 다양한 도심지의 상황을 상정한 Random, Mixed, Cluster 인스턴스로 구성되었다. 실험 결과 모든 인스턴스에서는 플렉스의 사용이 차량 유연 회차의 효율성을 높여주는 것을 확인하였다. 또 플렉스와 배송 지연 시간 비용에 대한 민감도 분석에서는 "유연 회차와 플렉스"가 차량만을 사용하는 방식의 차량 대수에 따라 값에 차이를 보였지만, 플렉스 비용이나 배송 지연 시간 비용이 200% 증가하는 경우에도 우위를 유지하는 것을 확인하였다. 본 연구의 결과는 플렉스가 차량과 연계되어 활용되는 경우, 플렉스에 의해 서비스되는 고객뿐만 아니라 차량으로 서비스되는 고객들의 서비스 품질을 높일 수 있음을 보여준다.